"Is hourly billing the best way to capture and communicate value in law firm pricing?" - Widdop, Anthony (2008)
The subject of legal fees and value goes right to the heart of the law firm-client relationship and in recent times has become a hot topic in the industry. With internal pressure on clients to manage costs in tough economic conditions, firms are being pushed to better demonstrate the value they create. At the centre of this debate is the current pricing standard, hourly billing.